2000
DOI: 10.2134/jeq2000.00472425002900030019x
|View full text |Cite
|
Sign up to set email alerts
|

17 β‐Estradiol as an Indicator of Animal Waste Contamination in Mantled Karst Aquifers

Abstract: The poultry and cattle industries comprise a large segment of the agricultural economy in the mantled karst area of northwest Arkansas. The associated risks of nutrient and bacterial contamination to karst aquifers by poultry litter have been well documented. However, only recently have the risks associated with hormones, specifically 17 β‐estradiol (E2), been addressed. During a winter recharge event, five springs in northwest Arkansas were sampled and the waters were analyzed for E2, fecal coliform, and Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 0 publications
1
92
1
6
Order By: Relevance
“…Peterson et al (2000) reported the presence of 17β-estradiol at concentrations ranging from 6 to 66 ng L -1 (6 to 66 ppt) in spring water discharged from a mantled karst aquifer in a region with intense poultry and cattle production facilities in northwest Arkansas. Arnon et al (2008) Though it may be difficult to assign a specific source in each case, one cannot ignore the link to animal production facilities.…”
Section: Major Scientific and Environmental Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peterson et al (2000) reported the presence of 17β-estradiol at concentrations ranging from 6 to 66 ng L -1 (6 to 66 ppt) in spring water discharged from a mantled karst aquifer in a region with intense poultry and cattle production facilities in northwest Arkansas. Arnon et al (2008) Though it may be difficult to assign a specific source in each case, one cannot ignore the link to animal production facilities.…”
Section: Major Scientific and Environmental Concernsmentioning
confidence: 99%
“…Presumably in combination with endogenous compounds, synthetic steroids, such as trenbolone acetate and melengestrol acetate, may be metabolized and released into the environment only through cattle manure (liquid or solid). Natural and synthetic steroids have been detected at varying concentrations in manure, lagoon effluent, soil profiles, and in surface and groundwater (Schiffer et al 2001;Hutchins et al 2007; Arnon et al 2008;Kolpin et al 2002;Peterson et al 2000). Several researchers have suggested possible adverse impacts of steroids in surface and groundwater including endocrine disrupting effects on aquatic life, animals, and possibly humans (Renner 2002;Raloff 2002;Falconer et al 2006).…”
mentioning
confidence: 99%
“…Estrogenic compounds, such as 17β-E2 have been shown to be mobile, and have been found in runoff from manured lands (Nichols et al, 1997), and in mantled karst aquifers (Peterson et al, 2000). Trenbolone metabolites have also been shown to be mobile, as dung piles released small amounts of TB metabolites in runoff following rain storms (Schiffer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier detections of several steroids before the tracer Br may be due to preferential flow (Kjaer et al, 2007;Wicks et al, 2004;Peterson et al, 2000). However, a few steroids that can be more persistent in the soil-water system, such as estrone or progesterone, along with other organic and inorganic compounds, may be a threat to groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Shore et al (1995) indicated that both testosterone and estrogen can leach from soil at varying rates and reach streams through subsurface and surface flow. Peterson et al (2000) reported the presence of 17β-estradiol at concentrations that ranged from 6 to 66 ng L -1 in spring water discharged from a mantled karst aquifer in a region with intense poultry and cattle feeding activities in northwest Arkansas. In a similar study, Wicks et al (2004) detected 17β-estradiol at concentrations ranging from 13 to 80 ng L -1 from eight springs that drain the Ozark Plateau Aquifer in the karstic basin near the Missouri-Arkansas border and concluded that the aquatic organisms living in the basin may be exposed to a 17β-estradiol concentration above 25 ng L -1 nearly 60% of the time.…”
mentioning
confidence: 99%